Transformation of Prison Staff Services towards Sustainable Professionalism and Job Satisfaction Development (Case Study of Class IIA Salemba Prison, Jakarta) - Pramesworo, Ignatius Septo; Markonah, Markonah; R, Hikmah A; Evi, Tiolina (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This activity involves cooperation with various parties, including correctional officers, professionals in the field of Education and the Government in this case the Ministry of Education, Research and Technology in the field of Community-Based Empowerment. Through this community service activity, it is expected that correctional officers can improve their capacity and welfare through various professional and personal development programs. This program is designed to support the effectiveness of officers' work and their work-life balance. In this training, it is explained how Service Excellence and Managerial Skills can be carried out. This training was delivered to officers in the service sector totaling 30 people who are ASN Salemba Prison. Participants are 25-33 years old with a Bachelor's degree in Law, Education, Economics and Social. Male participants 60% and female 40%. Among the participants were 2 structural officials. Preparation for the implementation was carried out in two meetings. The first meeting discussed the event rundown, division of tasks for each lecturer, provision of materials and preparation of questions to be asked to participants, availability of supporting equipment to make it easier for Prison 2A officers to listen to presentations from the Perbanas Institute. The second meeting involved the head of the Salemba Class IIA Prison who discussed the revised material and adjusted it to the situation at the Salemba Class IIA Prison. This Community Service Activity was carried out on Thursday, August 22, 2024 face-to-face and the material provided was about how IIA Prison officers provide the best service, improve employee managerial skills, and provide solutions to obstacles and results obtained from the situations discussed previously. The implementation went smoothly according to the predetermined schedule, the speakers delivered their materials according to the prepared concept, namely regarding service excellence and managerial skills.